Profil Sistem Energi Berbasis Saturasi Oksigen Otot (SmO₂) Atlet Bulutangkis Menggunakan Moxy Monitor untuk Pengkondisian Fisik - Irman Felisiana Miftahul Khoir; Jajat Darajat Kusumah Negara; Agus Gumilar (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2026)
This study aims to analyze the muscle oxygen saturation (SmO₂) profile of badminton athletes using the Moxy Monitor, to examine its relationship with the aerobic and anaerobic energy systems, and to evaluate its potential as a basis for designing physical conditioning programs. This study used a quantitative approach with a correlational method involving 10 badminton athletes from PB Mutiara Cardinal Bandung, selected through purposive sampling. Data were collected through SmO₂ measurements using the Moxy Monitor during physical testing, along with physical condition measurements based on biomotor parameters. Data were analyzed using descriptive statistics, the Shapiro-Wilk normality test, Pearson correlation, simple linear regression, multiple linear regression, and path analysis. The results showed that the SmO₂ Ratio had a significant relationship with aerobic capacity (r = 0.766; p = 0.010) and physical condition (r = 0.727; p = 0.017), but no significant relationship with anaerobic capacity (r = 0.361; p = 0.305). Aerobic capacity had a very strong relationship with physical condition (r = 0.966; p = 0.000), while anaerobic capacity also showed a significant relationship (r = 0.810; p = 0.004). These findings indicate that an SmO₂-based energy system profile can be used as a physiological indicator for designing more precise physical conditioning programs based on the individual needs of badminton athletes. Keywords: Badminton, Moxy Monitor, Physical Conditioning, Energy System, SmO₂